What teachers need to know about language - Adger, Carolyn Temple; Snow, Catherine E.; Christian, Donna (CAL series on language education, 2018)
This book shows what teachers need to know about language to work effectively with diverse students. It gives examples of the many aspects of teaching and learning in which language is a key, and it suggests how teacher education programs can help teachers gain the knowledge and skills they need to refine their practice.